Oil price shocks and stock return volatility: New evidence based on volatility impulse response analysis - Sercan Eraslan; Faek Menla Ali (Deutsche Bundesbank, 2018)
We use volatility impulse response analysis estimated from the bivariate GARCH-BEKK model to quantify the size and the persistence of different types of oil price shocks on stock return volatility and the covariance between oil price changes and stock returns for a wide range of net oil-importing and oil-exporting countries. We find that precautionary demand followed by aggregate demand-side shocks, compared to supply-side ones, have higher positive and persistent effects on the conditional variances of stock returns for all countries. Moreover, we show that precautionary demand shocks, unlike the other types of shocks, mostly affect the covariances between oil price changes and stock returns; their effects being negative for all countries except China, Norway and Russia, where they are positive.
Keywords: C32; Q43; 330; Oil price shocks; Stock returns; Volatility impulse response analysis